Non-Schrödinger Orbitals (Global Journal of Science Frontier Research, 2024)
Schr dinger s searchlight made it possible to enlighten the atom and cast shadows on the Screen of the Observer But the main trouble of the modern Quantum Theory is precisely that it mistook the shadows from the Elephant for the Elephant itself for Reality This led to a catastrophic discrepancy between the allowed calculated energy levels of electrons and the experimental ionization potentials with an increase in the mass of atoms But the inclusion of normal illumination - UNDERSTANDING gives a REAL Quantum Theory which can be built on the path laid by Planck-de Broglie-Einstein-Heisenberg-Bohm Quantization adds a new INVARIANT and strictly mathematically according to Planck expands complements the Classics and does not deny it - Resonant orbits of electrons in atoms - Electronic Orbitals correspond to resonant de Broglie waves And Pontryagin s Dualism of Functional Sets translates Schr dinger s Uncertainty Principle into the Principle of CERTAINTY OBSERVABILITY
Keywords: classical orbit; ionization potential; planck resonance; de broglie waves